Accumulation of vulnerabilities in the aftermath of the 2015 Nepal earthquake: Household displacement, livelihood changes and recovery challenges. (October 2018) - He, Lulu; Aitchison, Jonathan C.; Hussey, Karen; Wei, Yongping; Lo, Alex
Abstract: Vulnerability refers to conditions which increase the susceptibility of a community to the impact of hazards. This study applies the concept of vulnerability to a disaster fact in order to demonstrate why people are vulnerable and how the vulnerability plays its role in impeding the recovery from disaster impacts. We advance with a framework depicting that the 2015 Nepal earthquake perpetuated the vulnerabilities of rural households. At the study area Barpak VDC, 82 displaced households from five temporary shelter sites were interviewed with a semi-structured questionnaire. Documents from the VDC office and district government were reviewed. With a descriptive approach to processing data, our study finds that vulnerability of these households have accumulated over time: (i) The pre-earthquake disadvantages poorly prepare them for adapting to disasters and adversely militate their recovery; (ii) The immediate impacts of the earthquake including asset loss and damage, and livelihood interruptions deprived households of vital entitlements that could have been relied on for recovery; and (iii) The temporary relocation rises challenges of people's health and permanent residence, which further exacerbates the vulnerability. Synthesis of these conditions is subsequently manifest in the ultimate adversity to recover from the earthquake impacts, generating a risk that people may become more disadvantaged in the future. Data suggest that successful recovery from the earthquake demands more comprehensive reconstruction tasks than solely rebuilding houses, and that a community-centered approach should be incorporated in the overall government reconstruction policy aiming at building local capacity in order to minimize vulnerability in the long term. This study revealed circumstances at the onset of recovery after a disaster event in a lower-income and landlocked nation, which can be used as a reference for disaster management in developing countries in the Himalayan region where is prone to natural hazards. Highlights: Disaster research on Nepal is of significance to risk reduction at the global scale. The accumulation of vulnerability impedes recovery from disaster impacts. There is a risk that people become more disadvantaged in years after the earthquake. Reconstruction in Nepal can only be successful by addressing such vulnerabilities.